10 Preliminary evaluation on phantom for the transmission detector Delta4 Discover for the VMAT treatments. (December 2018) - Mana, A.; Gautier, M.; Feuillade, J.; Burgaud, L.; Colnard, C.; Dejean, C.
Abstract : Introduction: To evaluate the Delta4 Discover behavior during the VMAT treatments deliverance and to determine the error detection thresholds. Methods: The transmission detector Discover (Scandidos) is placed at the exit of the beam on Clinac 2100C Varian with Millenium MLC 120 leaves. It is composed of 4040 diodes with a 1 mm diameter, spaced 5 mm perpendicularly to the leaves movement and 2.5 mm in the same direction than the leaves movement and covering a 19.5 cm x 25 cm field size. The attenuation has been measured with 6 and 18MV beams at isocenter (field size 10 cm x 10 cm at a depth of 10 cm). The system repeatability has been evaluated to control 3 VMAT treatment plans. It was also measured by sequentially inserting different errors like leaves position, change of energy, depth, thickness and patient positioning. The errors of leaves position have been inserted for 3 leaves pairs on 4 control points of each beam. The following parameters can be analyzed: -The index gamma of dose distribution (3%-3 mm) -The delivered dose in function of angulation gantry ( Δ = ± 1%) -The angulation collimator ( Δ = ± 1°) -The MLC index gamma: the beam signal integrated every 25 ms measuring the gantry angulation and the end leaves position. Results: The measured attenuation is 1.6% in 6MV and 0.9% in 18MV. The repeatability results show an average standard deviation of 0.7% and maximum at 1.6% for 3 treatment plans with gamma index calculation. The results systematically decrease of more than 80% in the gamma index score when the energy of treatment plans has been changed. The results bring out a difference from −6% to −8% with gap of leaves position superior at 2 mm on a beam with 12 inserted mistakes: -5 are > 2 mm -5 are between 1 mm and 2 mm -2 are < 1 mm The leaves whose positions are not those expected are correctly identified. Conclusions: The Discover system is an advantage for pre- and per-treatment control of patients treated with VMAT. The attenuation modeling directly in the TPS is also an advantage for a daily use on the entire treatment. All measured parameters may show discrepancies or predict premature wear of certain components of the collimator.